A review of the essential concepts in diagnosis, therapy, and gender assignment in disorders of sexual development - Sarma, Vivek Parameswara (Annals of Pediatric Surgery, 2022)
Background The aim of this article is to review the essential concepts, current terminologies and classification, management guidelines and the rationale of gender assignment in different types of differences/disorders of sexual development. Main body The basics of the present understanding of normal sexual differentiation and psychosexual development were reviewed. The current guidelines, consensus statements along with recommendations in management of DSD were critically analyzed to formulate the review. The classification of DSD that is presently in vogue is presented in detail, with reference to old nomenclature. The individual DSD has been tabulated based on various differential characteristics. Two schemes for analysis of DSD types, based on clinical presentation, karyotype and endocrine profile has been proposed here. The risk of gonadal malignancy in different types of DSD is analyzed. The rationale of gender assignment, therapeutic options, and ethical dimension of treatment in DSD is reviewed in detail. Conclusion The optimal management of different types of DSD in the present era requires the following considerations: (1) establishment of a precise diagnosis, employing the advances in genetic and endocrine evaluation. (2) A multidisciplinary team is required for the diagnosis, evaluation, gender assignment and follow-up of these children, and during their transition to adulthood. (3) Deeper understanding of the issues in psychosexual development in DSD is vital for therapy. (4) The patients and their families should be an integral part of the decision-making process. (5) Recommendations for gender assignment should be based upon the specific outcome data. (6) The relative rarity of DSD should prompt constitution of DSD registers, to record and share information, on national/international basis. (7) The formation of peer support groups is equally important. The recognition that each subject with DSD is unique and requires individualized therapy remains the most paramount.